2016
DOI: 10.1111/rec.12374
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects of vegetational restoration on soil microbial communities on the Loess Plateau of China

Abstract: Soil microbial communities are important indicators for evaluating the effectiveness of vegetational restoration. The ability of soil microbial communities to recover under six types of restoration was examined using Biolog, phospholipid fatty acid (PLFA), and denaturing gradient gel electrophoresis (DGGE). Soil samples were collected from eroded loessial soils that had been restored for 30 years on the Loess Plateau with natural grass, black locust, korshinsk peashrub, Chinese pine, and mixed forest of Chines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 72 publications
4
10
1
Order By: Relevance
“…Guo [28] found a higher abundance of Firmicutes and lower abundance of Proteobacteria and Actinobacteria in cropland than in the restoration site, which is in accordance with our result. However, the higher frequency of Firmicutes in the studied site was in sharp contrast to the relatively lower abundance reported in other studies [29][30][31]; this is mainly due to the high abundance of Bacillus. Firmicutes, typically Bacillus and its derived genera, are a group of aerobic endospore-forming bacteria abundant in soils [36].…”
Section: Bacterial Communities Along Agroforestry Chronosequencecontrasting
confidence: 99%
See 1 more Smart Citation
“…Guo [28] found a higher abundance of Firmicutes and lower abundance of Proteobacteria and Actinobacteria in cropland than in the restoration site, which is in accordance with our result. However, the higher frequency of Firmicutes in the studied site was in sharp contrast to the relatively lower abundance reported in other studies [29][30][31]; this is mainly due to the high abundance of Bacillus. Firmicutes, typically Bacillus and its derived genera, are a group of aerobic endospore-forming bacteria abundant in soils [36].…”
Section: Bacterial Communities Along Agroforestry Chronosequencecontrasting
confidence: 99%
“…Diversified plant species and the resultant rhizosphere chemistry and litter quality could affect the soil microbial community [28]. Some previous studies in the same region found that microbial diversity increased with afforestation [29][30][31], and the microbial diversity associated with the aboveground vegetation. Zhang [32] observed that soil bacterial diversity decreased at the early stage of restoration on farmland along with the aboveground vegetation decrease.…”
Section: Bacterial Communities Along Agroforestry Chronosequencementioning
confidence: 99%
“…Although relatively similar in richness, the community composition of total fungi and major functional guilds (ECM and SAP) in SF were still divergent from those in PF after 20 years of reforestation. These findings support our second hypothesis, and agree with Xiao et al (2016) who showed that soil microbial communities do not fully recover 30 years after the reforestation of farmland in Shanxi China. In contrast, based on fungal sporocarp data, Oria-de-Rueda et al (2010) showed that abandoned farmland dominantly reforested with Pinus spp.…”
Section: Effects Of Land-use Type On Fungal Communitiessupporting
confidence: 93%
“…Other studies have demonstrated that microaggregates are rich in small pores with diameters of <0.2 μm, and small pores are thought to be effective in preventing internal organic carbon decomposition by bacteria. Small pore structures are also stable and difficult to destroy (Xiao, Liu, Zhang, & Xue, ). Simultaneously, plant root systems can act as ecosystem engineers to reduce water‐induced soil erosion by sequestering more SOM into soil, thereby improving its hydrological properties (Eldridge, ).…”
Section: Discussionmentioning
confidence: 99%